Silicon Nanowires for Green Energy Applications - Sivasubramanian, Maharajan; W. Lo, Leu (Current Organic Chemistry, 2014)
In recent decades, vast developments in materials science and technology have resulted in the creation of nanomaterials with sophisticated architectures. The diverse potentials of these nanomaterials have been well-recognized and studied in various areas, including chemistry, biology, physics and energy. Although several nanomaterials have been intensely investigated for energy applications, the interest in silicon nanowires (SiNWs) as potential building blocks in the renewable energy arena has greatly increased. The emergence of SiNWs use is primarily due to the ability to tailor their properties, such as chemical composition, structure and morphology, during their growth or etching process. This ease of modification has resulted in the development of functional devices for a number of applications, including solar cells, photoelectrochemical conversion, lithium ion batteries and field-effect transistors. In this review, we present several important applications of SiNWs in solar cells, lithium ion batteries and photoelectrochemical conversion for renewable energy applications.
Keywords: solar cells